Intensity of Nematode Infection in Children Aged 3 to 5 Years Living in Mukuru Kwa Njenga Slum Settlement, Nairobi, Kenya - Lynda Allan; Fiona N. Mbai; Dorcas S. Yole; Moses Owino (Journal of Tropical Medicine)
Background. The burden of nematode infections is high mostly in children below 5 years old, with clinical manifestations ranging from mild to painful symptoms due to severe infections that end up suppressing the immune system of the infected children. The occurrence of these infections is highest in areas of extreme poverty. This study evaluated the intensity of nematode infections and assessed the status of deworming in children aged 3 to 5 years living in Mukuru slum settlement, Nairobi County, Kenya. Methodology. A total of 172 children aged between 3 and 5 years were sampled across the 5 major villages of Mukuru Slum settlement: Kwa Njenga, Vietnum, Wapewape, Kwa Reuben, and Motomoto. Community health workers administered questionnaires on the deworming history of children. Stool samples were collected, macroscopically examined, and microscopically analysed using Kato-Katz technique to assess the intensity of infection. The intensities of nematode infections were expressed as eggs per gram (epg) of faeces. Results. The point prevalence of nematode infection among the 98 children in the 1st sampling was 25.5% with a mean infection intensity of 5424 epg, whereas among the 74 children sampled in 2nd sampling, 47.3% had nematode infection with a mean infection intensity of 12384 epg. The average nematode infection for the 172 participants was 34.9% with a mean intensity of 17808 epg. The highest number of children infected with nematodes was in the village of Wapewape where 34 participants were examined and 36.3% were infected with a mean intensity of 3216 epg. Kwa Reuben and Vietnum villages had the same prevalence values of 32.4% where 34 participants in each village had a mean intensity of 3624 epg and 4512 epg, respectively. In both samplings, more than 80% of children had been dewormed more than 6 months prior to the study. Ascaris lumbricoides was the only species of intestinal nematodes identified to be present in the stool samples of children in this study, whereas Trichuris trichiura and hookworm infections were found to be absent. The intensity of infection was not dependent on age or gender.